Pengaruh Motivasi Eksternal oleh Guru Pendidikan Agama Kristen Terhadap Sikap Belajar Siswa Kelas VII SMP N 1 Harian Tahun Pembelajaran 2022/2023 - Dessi Simorangkir; Hasudungan Simatupang; Sudirman Lase (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to determine the influence of external motivation by Christian religious education teachers on the learning attitudes of Class VII students at SMP N 1 Harian for the 2022/2023 academic year. The research method used is a quantitative method. The population is all 40 students of Class VII of SMP N 1 Harian. Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.608 > rtable(=0.05,n=40) = 0.312. b) Testing a significant relationship obtained tcount= 4.719 > ttable(=0.05, dk=n-2=38)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="13.29"+0.78X. b) Regression coefficient of determination test (r2) = 36.9%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=20, dk denominator=n-2=40-2=38) namely 22.26 > 1.51. Thus Ha is accepted and H0 is rejected.